2000
DOI: 10.1182/blood.v95.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the soluble granulocyte-macrophage colony stimulating factor receptor protein in vivo

Abstract: On the basis of the finding of alternatively spliced mRNAs, the -subunit of the receptor for GM-CSF is thought to exist in both a membrane spanning (tmGMR) and a soluble form (solGMR). However, only limited data has been available to support that the solGMR protein product exists in vivo. We hypothesized that hematopoietic cells bearing tmGMR would have the potential to also produce solGMR. To test this hypothesis we examined media conditioned by candidate cells using functional, biochemical, and immunol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…1999). The CRT‐MG human astroglial cells and U937 human monocytic cells were maintained in RPMI 1640 medium with 10 mmol/L HEPES (pH 7.2) supplemented with 2 mmol/L l ‐glutamine, 100 U/mL penicillin, 100 μg/mL streptomycin (Gibco BRL, Grand Island, NY, USA), and 10% heat‐inactivated fetal bovine serum, as previously described (Sayani et al. 2000; Choi et al.…”
Section: Methodsmentioning
confidence: 99%
“…1999). The CRT‐MG human astroglial cells and U937 human monocytic cells were maintained in RPMI 1640 medium with 10 mmol/L HEPES (pH 7.2) supplemented with 2 mmol/L l ‐glutamine, 100 U/mL penicillin, 100 μg/mL streptomycin (Gibco BRL, Grand Island, NY, USA), and 10% heat‐inactivated fetal bovine serum, as previously described (Sayani et al. 2000; Choi et al.…”
Section: Methodsmentioning
confidence: 99%
“…Death receptors and perhaps other surface molecules are able to activate SHP‐1, which can also inhibit survival factor signaling. Moreover, survival factor‐mediated effects can be reduced by soluble cytokine receptors (117) or anti‐inflammatory cytokines and elimination of the pathogen results in reduced survival factor production. Finally, anti‐inflammatory drugs often modify the production of pro‐inflammatory cytokines.…”
Section: Potential Mechanisms That Limit Neutrophil Antiapoptosismentioning
confidence: 99%
“…It has previously been demonstrated that solGMRα was found in serum samples obtained from healthy donors with a normal range of 10–85 pmol/l (Sayani et al, 2000). In the same study, four of five patients with AML demonstrated elevated solGMRα levels (Sayani et al, 2000). The elevated solGMRα levels in that small cohort of AML patients suggested a pathophysiological role for solGMRα in leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of solGMRα levels in serum has been determined in the normal population (Sayani et al, 2000) and has a range of 10–85 pmol/l. In our study, solGMRα levels less than 10 pmol/l were considered low and levels greater than 85 pmol/l were considered high.…”
Section: Solgmrα Level Distribution According To Haematological Maligmentioning
confidence: 99%
See 1 more Smart Citation